New grading system for post-COVID-19 pulmonary fibrosis based on computed tomography findings. Issue 35 (2nd September 2022) - Demircioglu, Ozlem; Kocakaya, Derya; Cimsit, Canan; Cimsit, Nuri Cagatay
Abstract : Background: There is currently no objective computed tomography (CT)-defined grading system for coronavirus disease (COVID-19)-related pulmonary fibrosis. We propose a CT-based radiological scale that adapts the histological fibrosis scale to pulmonary fibrosis CT findings, to evaluate possible predictive factors for the degree of fibrosis in these patients. Methods: A new radiological fibrosis grading system was created based on existing histological fibrosis scales. One hundred forty-seven COVID-19 patients with any degree of fibrosis on CT were evaluated. Smoking status, the presence of hypertension, the duration of hospital stays, the presence of comorbid diseases, and the levels of prognostic and predictive factors for COVID-19 were evaluated, and how these parameters affected the fibrosis scores was examined. Results: Of 147 patients, 17.7% had grade 1, 17% had grade 2, 51.7% had grade 3, and 13.6% had grade 4 fibrosis. ANOVA revealed statistically significant relationships between the fibrosis scores and lactate dehydrogenase values, lymphocyte count, C-reactive protein level, and length of hospital stay. Smoking, advanced age, hypertension, and male sex showed significantly higher scores for fibrosis. Conclusions: Using our CT-defined lung fibrosis grading system, we could predict the severity of fibrosis as well as the resultant lung pathology in COVID-19 patients. Thus, disease exacerbation and development of permanent severe fibrosis can be prevented using the appropriate treatment methods in high-risk patients.